Surface modification of multiwalled carbon nanotubes by chemical oxidation and immobilization of tyrosinase - Mohammad Sabri, Nur Anis (2012)
Studies on the development of interface between biological molecules and novel nanomaterials have attracted research worldwide. Carbon nanotubes (CNTs) have become an important matrix for the fabrication of biomaterials due to its unique properties. Surface properties of the CNTs and the medium of immobilization are critical in the immobilization of enzymes. In this study surface modification of multi-walled carbon nanotubes (MWCNTs) for carboxylic moieties attachment was accomplished by acid treatment and reaction with potassium permanganate (KMnO4). The effect of these two oxidants on the surface modification of MWCNTs for tyrosinase immobilization was studied. Commercial MWCNTs were treated with either concentrated sulfuric acid - nitric acid mixture of ratio 3:1 or 0.1 M KMnO4 via reflux, stirring and ultrasonication. The resulting surface modified MWCNTs were characterized with FT-IR spectrophotometer, XPS, and FESEM. The immobilized tyrosinase was tested for leaching assay and its catalytic activity towards phenol was analysed. The FTIR spectra of functionalized MWCNTs showed a significance peak in the range of 1700 cm-1 to 1729 cm-1 indicating the presence of carboxyl double bond, which confirmed the successful functionalization of MWCNTs (FCNTs) by chemical oxidation. The carboxylic peak of MWCNTs treated with KMnO4 (FCNTK) showed higher intensity as compared to acid-treated MWCNTs (FCNTA). These results are supported with the shift of O 1s binding energy at 534.9 eV and shoulder of C 1s at 289.00 eV corresponding to carboxylic groups from XPS analysis. The immobilization of tyrosinase onto FCNTA is higher than FCNTK with high catalytic activity for phenol degradation. Further sorption study showed that FCNTA with immobilized tyrosinase (FCNTA-Ty) has higher sorption towards phenol as compared to FCNTA and pristine MWCNTs. The results illustrated that FCNTA-Ty, FCNTAs and MWCNTs had relatively well adsorption capacity for phenol as described by both Langmuir and Freundlich models. In addition, the adsorption kinetics for these CNTs were well fitted with the pseudo-second order model with reasonably good correlation coefficient. This study led to possible application of bioremediation of phenol in industrial sample by attaching the FCNTA-Ty onto chitosan.